2007
DOI: 10.1044/1058-0360(2007/020)
|View full text |Cite
|
Sign up to set email alerts
|

African American English Dialect and Performance on Nonword Spelling and Phonemic Awareness Tasks

Abstract: After Grade 2, nonword spelling may be more sensitive to the effects of dialect variation than are phonemic awareness tasks. It is suggested that spelling may be a more sensitive clinical indicator of difficulties in integrating the phonological and orthographic information needed for fluent decoding skill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…Finally, a number of AAE studies have shown that children vary in the rate (i.e., density) at which they produce nonmainstream grammatical structures (Craig, Zhang, Hensel, & Quinn, 2009;HortonIkard et al, 2005;Jackson & Roberts, 2001;Kohler et al, 2007;Oetting, 2005;Oetting et al, 2010;Pruitt & Oetting, 2009;Terry, Connor, Thomas-Tate, & Love, 2010;Van Hofwegen & Wolfram, 2010). However, the relationship between children's nonmainstream dialect densities and their use of individual grammatical structures is unclear.…”
Section: Previous Studies Of Child Aaementioning
confidence: 93%
“…Finally, a number of AAE studies have shown that children vary in the rate (i.e., density) at which they produce nonmainstream grammatical structures (Craig, Zhang, Hensel, & Quinn, 2009;HortonIkard et al, 2005;Jackson & Roberts, 2001;Kohler et al, 2007;Oetting, 2005;Oetting et al, 2010;Pruitt & Oetting, 2009;Terry, Connor, Thomas-Tate, & Love, 2010;Van Hofwegen & Wolfram, 2010). However, the relationship between children's nonmainstream dialect densities and their use of individual grammatical structures is unclear.…”
Section: Previous Studies Of Child Aaementioning
confidence: 93%
“…DDMs seem to capture differences in the quantity of NMAE related to age or grade Horton-Ikard & Ellis Weismer, 2005), sampling contexts (Horton-Ikard & Miller, 2004;Washington, Craig, & Kushmaul, 1998), and even NMAE varieties (Oetting & McDonald, 2002). They also have been used with children from diverse economic backgrounds (Horton-Ikard & Miller, 2004;Washington & Craig, 1994) and across oral and literate contexts (Horton-Ikard & Pittman, 2010;Ivy & Masterson, 2012;Kohler et al, 2007;Thompson et al, 2004).…”
Section: Dialect Measuresmentioning
confidence: 95%
“…LJTs and TKBMs such as the DDMu or DDMw have been highly correlated with one another (Oetting & McDonald, 2002). Each of these measures has proven to be useful across a number of investigations with a variety of age groups and for a variety of purposes (e.g., Craig & Grogger, 2012;Ivy & Masterson, 2012;Kohler et al, 2007). However, whether these new indices are similarly consistent and whether, collectively, their utility for characterizing NMAE does indeed vary by children's grade level, remains unknown.…”
Section: Comparisons Across Indicesmentioning
confidence: 97%
“…Two separate studies (Craig, Thompson, Washington, & Potter, 2004;Craig, Zhang, Hensel, & Quinn, 2009) used a subsample of a larger study , but investigated different outcomes, and these three were combined to form one study. Another three studies provided outcomes disaggregated by grade level (Charity, Scarborough, & Griffin, 2004, Grades K-2; Kohler et al, 2007, Grades 1 and 3; Terry, 2006, Grades 1-3), resulting in a total of 20 observed study effect sizes. From these studies, 75 outcome effect sizes were coded: 59 for reading and 16 for writing and spelling; a simple mean was computed for the study's overall effect size.…”
Section: Description Of Studiesmentioning
confidence: 99%